LOCAL PERSPECTIVES ON COMMUNITY-DRIVEN MARINE DEBRIS MANAGEMENT FOR SUSTAINABLE TOURISM IN THE ANDAMAN ISLANDS, THAILAND - Chanisada CHOOSUK; Prawit KHUNNIKOM; Thitichaya BOONSOM; Somporn KHUNWISHIT; Poonyanuch RUTHIRAKO; Narun NATTHAROM; Jitrawadee THITINANTHAKORN (Geo Journal of Tourism and Geosites)
Community-driven marine debris management is key to sustainable island tourism. This qualitative research aimed to explain perspectives on waste management for sustainable tourism, via two case studies of Andaman Islands. Data were collected by reviewing secondary data, in-depth interviews, and focus group discussions with nineteen key informants: 6 marine debris collectors, 6 community leaders, 5 entrepreneurs, and 2 government officers. Content and narrative analyses were applied. Marine debris management comprised 2 main perspectives with 4 minor perspectives, valuable for policy and long-term planning. Notably, understanding internal factors like beliefs and motivations towards sustainability is crucial for effective waste management strategies.